2006
DOI: 10.1213/01.ane.0000189556.49429.16
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic Temperature Measurement Compared with Pinprick and Cold Sensation in Predicting the Effectiveness of Regional Blocks

Abstract: We designed this study to evaluate the usefulness of thermographic temperature measurement with an infrared camera, compared with patient response to cold and pinprick, as a means of assessing the success or failure of axillary blockades. Axillary blocks were performed on 25 patients undergoing surgery on the hand or forearm using a nerve stimulator technique with mepivacaine 1.5%. Pinprick and cold sensation were assessed on the operative site at 5-min intervals for 30 min. A thermographic image of the operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 12 publications
0
65
1
5
Order By: Relevance
“…There were 7 men and 1 woman with a mean (SD) age of 47 (16) years, weight of 66 (2.3) kg, height of 172 (5) cm, and a body mass index 22.4 (1.6) kg/m 2 . All the axillary BPBs were successful and provided adequate surgical anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…There were 7 men and 1 woman with a mean (SD) age of 47 (16) years, weight of 66 (2.3) kg, height of 172 (5) cm, and a body mass index 22.4 (1.6) kg/m 2 . All the axillary BPBs were successful and provided adequate surgical anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that a noncontact infrared temperature probe may provide an easier and less expensive tool to use in clinical practice, although previous investigations described conflicting results for the evaluation of nerve blocks of the lower extremities. [2][3][4] The aim of the study was to determine whether an infrared thermometer can be used as a reliable method to predict block success, defined as complete sensory block after infraclavicular brachial plexus block. 5…”
mentioning
confidence: 99%
“…[3] Other research showed that the temperature rise in the limb is general when performing an axillary plexus block. [4] In studies by Werdehausen et al and Stevens et al the rise in skin temperature after epidural, spinal and combined sciatic and femoral blocks showed an evident proximal to distal gradient. [7,8] However, because a whole limb was blocked, no definite statement could be made on the difference in temperature effects of the sciatic and femoral nerve.…”
Section: Discussionmentioning
confidence: 94%
“…Sensory assessment was performed by systematic pinprick testing with a 24G needle, consecutively from the lateral side of the lower leg (below the knee) over the lateral malleolus to the heel (1), the dorsal and lateral side of the foot (2), every toe separately (3), the plantar side of the foot (4). Results where noted as 'sharp' = 'normal' = 'positive' or 'numb' = 'negative'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation